Alkaline electrolytic water hydrogen production diaphragm capable of strengthening hydroxyl ion transfer and preparation method of alkaline electrolytic water hydrogen production diaphragm

By constructing a hydrogen bonding network and providing a hydrophilic gas barrier coating in the alkaline electrolytic water hydrogen production separator, the contradiction between high air tightness and low surface resistance of existing separator materials is solved, and low energy consumption and high gas barrier properties are achieved. Separator performance of tightness and good mechanical strength.

CN119332303APending Publication Date: 2025-01-21XIAN TAIJIN NEW ENERGY & MATERIALS SCI TECH CO LTD

Patent Information

Application Number
CN202411449128.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing alkaline electrolytic water hydrogen-making diaphragm materials maintain high airtightness while maintaining high airtightness, it is difficult to effectively reduce surface resistance and electrolytic energy consumption, and the mechanical strength is insufficient.

Method used

Polar groups such as hydroxyl groups, amino groups, and carboxyl groups are introduced into the traditional composite separator to build a hydrogen bond network and strengthen hydroxide ion transmission. Hydrophilic gas barrier coatings are also provided on both sides of the separator, including hydroxyl ion transfer carriers, Polymer binder and hydrophilic metal oxide particles.

Benefits of technology

It is possible to maintain high air tightness while reducing the surface resistance of the diaphragm, reducing electrolysis energy consumption, and improving the mechanical strength and ion transmission capacity of the diaphragm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332303A_ABST
    Figure CN119332303A_ABST
Patent Text Reader

Abstract

The invention discloses an alkaline electrolytic water hydrogen production diaphragm for strengthening hydroxyl ion transfer and a preparation method of the alkaline electrolytic water hydrogen production diaphragm. The diaphragm comprises a supporting base net and a hydrophilic gas insulation coating which is arranged on the supporting base net and contains a hydroxyl ion transfer carrier, the method comprises the steps that a supporting base net is pretreated; the preparation method comprises the following steps: dissolving a polymer binder, a pore-foaming agent, a hydroxyl ion transfer carrier and a hydrophilic metal oxide in an organic solvent according to a mass ratio to obtain hydrophilic slurry; uniformly coating two sides of a supporting base net with the hydrophilic slurry, and then carrying out non-solvent induced phase conversion to obtain the alkaline electrolytic water hydrogen production diaphragm for strengthening hydroxyl ion transfer; polar groups such as hydroxyl, amino and carboxyl are introduced into a traditional composite diaphragm to construct a hydrogen bond network, so that hydroxyl ions can be transmitted in a jumping manner along the dynamic hydrogen bond network in the diaphragm to promote transmission of the hydroxyl ions, the performance of the diaphragm can be improved, the materials are cheap and easy to obtain, the preparation process is simple and convenient, and industrial expanded production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of membrane materials for hydrogen production by water electrolysis, and in particular to an alkaline membrane material for hydrogen production by water electrolysis for strengthening hydroxide ion transfer and a preparation method thereof. Background Art

[0002] At present, the diaphragm materials in domestic alkaline hydrogen production electrolyzers are mainly asbestos and polyphenylene sulfide woven cloth. Among them, asbestos diaphragms are gradually withdrawn from the stage of history due to their carcinogenicity, easy pollution, high energy consumption and other problems; polyphenylene sulfide woven cloth has a micron-level pore size, which is difficult to effectively isolate the gas, and its high resistance leads to increased energy consumption in the electrolysis process. Therefore, it is very necessary to develop new diaphragm materials.

[0003] Polysulfone (PSF) is a type of high molecular polymer with phenylene sulfone as the structural unit, among which bisphenol A type polysulfone is the most widely used. It has the advantages of strong acid and alkali corrosion resistance, oxidation resistance, thermal stability and excellent mechanical properties. Compared with polyphenylene sulfide, polysulfone also has good solubility and is compatible with a variety of membrane making processes. It is considered to be applied to alkaline water electrolysis hydrogen production diaphragms.

[0004] Chinese invention patent application CN114432905A discloses a non-asbestos alkaline water electrolysis composite diaphragm and a preparation method thereof. The process steps of the application include: (1) preparation of casting solution; (2) preparation of polysulfone / zirconium dioxide composite diaphragm; (3) post-treatment of polysulfone / zirconium dioxide composite diaphragm; the patent application uses zirconium oxide to hydrophilically modify the polysulfone diaphragm, and prepares the membrane by immersion precipitation phase transformation method to obtain a composite diaphragm, thereby improving the hydrophilicity of the diaphragm, thereby effectively reducing the surface resistance and improving the current efficiency. However, the mechanical strength of the diaphragm is less than 3MPa, which is difficult to be used in practice.

[0005] Chinese invention patent CN115074763A discloses a preparation method and a diaphragm for producing hydrogen by electrolysis of alkaline water, and the preparation method comprises the following steps: S1, processing a polymer into a film; S2, etching through holes in the film by laser etching, wherein the maximum diameter of the through holes is between 10 nanometers and 500 micrometers; S3, coating the outer surface of the film obtained by processing step S2 with a hydrophilic coating to obtain a porous diaphragm for producing hydrogen by electrolysis of water; the method etches through holes in the polymer film by laser etching, effectively avoiding the interpenetration of hydrogen and oxygen, while ensuring that the electrolyte passes through the diaphragm smoothly, and finally coating the hydrophilic coating on the surface of the diaphragm to improve its ion transport performance. However, this film making method has a contradiction between low resistance and high air tightness, which requires different through hole diameters. High air tightness requires a smaller diameter of the etched through hole, while low resistance requires a higher porosity and through hole diameter. Therefore, how to strengthen the transfer of hydroxide ions in the membrane, reduce the surface resistance, and thus reduce the energy consumption of electrolysis while maintaining high air tightness is still a technical problem in this technical field. Summary of the invention

[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer and a preparation method thereof, by constructing a hydrogen bond network in the diaphragm to enhance hydroxide ion transfer, thereby effectively reducing the diaphragm surface resistance while maintaining high air tightness of the diaphragm, thereby reducing electrolysis energy consumption, and having the characteristics of strong ion transmission ability, good gas barrier performance and good mechanical strength.

[0007] The present invention introduces polar groups such as hydroxyl, amino, and carboxyl groups into the traditional composite membrane to construct a hydrogen bond network, so that hydroxide ions can be transferred in the membrane along the dynamic hydrogen bond network to promote hydroxide ion transfer and ultimately improve the membrane performance.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] An alkaline water electrolysis hydrogen production diaphragm for strengthening hydroxide ion transfer comprises a supporting base net 1, and hydrophilic gas barrier coatings 2 containing hydroxide ion transfer carriers are respectively arranged on both sides of the supporting base net 1.

[0010] The material of the supporting base net 1 is any one of polyphenylene sulfide, polypropylene or polytetrafluoroethylene.

[0011] The pore size of the supporting base mesh 1 is 200-500 μm.

[0012] The hydrophilic gas barrier coating 2 includes a hydroxide ion transfer carrier, a polymer binder and hydrophilic metal oxide particles; the hydrophilic slurry includes a polymer binder, a porogen, a hydroxide ion transfer carrier and hydrophilic metal oxide particles in a mass ratio of (15-30):(5-30):(0-30):(30-60).

[0013] The hydroxide ion transfer carrier is any one of polybenzimidazole, polyethylene glycol, polyvinyl alcohol, polyethyleneimine or layered double metal hydroxide additives or any combination of two or more thereof.

[0014] The polymer binder is any one of polysulfone, polyphenylsulfone or polyethersulfone or a combination of two or more of them in any ratio.

[0015] The hydrophilic metal oxide particles are any one of zirconium oxide, titanium oxide, magnesium oxide, cerium oxide, barium sulfate or barium titanate, or any combination of two or more thereof.

[0016] The particle size of the hydrophilic metal oxide particles is 50 to 200 nm.

[0017] A method for preparing an alkaline water electrolysis hydrogen production diaphragm for enhancing hydroxide ion transfer comprises the following steps:

[0018] Step S1: pre-processing the supporting base network 1:

[0019] Use deionized water or ethanol to remove impurities and dust on the surface of the support base mesh;

[0020] Step S2, preparing hydrophilic slurry:

[0021] The polymer binder and the porogen are dissolved in a good solvent for later use; the hydrophilic metal oxide particles and the hydroxide ion transfer carrier are evenly dispersed in the good solvent in which the polymer binder and the porogen are dissolved to obtain a hydrophilic slurry;

[0022] Step S3: coating the hydrophilic slurry on both sides of the supporting base mesh 1:

[0023] The hydrophilic slurry obtained in step S2 is evenly coated on both sides of the support base mesh 1 to obtain a thickness of 400 ~ 600μm liquid film;

[0024] Step S4, performing phase transformation on the hydrophilic slurry layer to form a hydrophilic air barrier coating 2:

[0025] The liquid film obtained in step S3 is subjected to a steam-induced phase transformation for 5-120 seconds and then immersed in a coagulation bath for a non-solvent-induced phase transformation. The coagulation bath temperature is between 10-60° C. and the non-solvent-induced phase transformation time is 10-60 minutes, forming a hydrophilic gas barrier coating 2 on both sides of the support base mesh;

[0026] Step S5, post-processing the diaphragm:

[0027] The membrane obtained in step S4 is immersed in deionized water to remove the good solvent used in preparing the hydrophilic slurry in the membrane, thereby obtaining an alkaline water electrolysis hydrogen production membrane with enhanced hydroxide ion transfer and a thickness of 300 to 600 μm.

[0028] The porogen in step S2 is polyvinyl pyrrolidone.

[0029] The good solvent in step S2 is one of N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylformamide.

[0030] The hydrophilic slurry in step S2 includes a polymer binder, a porogen, a hydroxide ion transfer carrier and hydrophilic metal oxide particles in a mass ratio of (15-30):(5-30):(0-30):(30-60).

[0031] The viscosity of the hydrophilic slurry in step S2 is 10-25 Pa·s.

[0032] The coating method in step S3 is scraping, dipping, spin coating, spraying or casting.

[0033] The coagulation bath in step S4 is preferably deionized water.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1. The present invention is based on the traditional composite membrane, in which a hydroxide ion transfer carrier is added. The polar groups contained in the carrier form a rich hydrogen bond network with the water molecules in the membrane channel, which promotes the rapid transfer of hydroxide ions through the breaking and reconstruction of hydrogen bonds. The formed membrane has a high hydroxide ion transfer capacity while maintaining the advantage of high airtightness;

[0036] 2. The hydrogen production membrane provided by the present invention is composed of a support layer and hydrophilic gas barrier coatings on both sides thereof, wherein the support layer is conducive to enhancing the mechanical strength of the membrane, the introduction of the hydroxide ion transfer carrier in the hydrophilic gas barrier coating is conducive to reducing the membrane surface resistance, and the appropriate pore structure in the coating is conducive to ensuring the air tightness of the membrane;

[0037] 3. The preparation materials required for the hydrogen production membrane preparation method provided by the present invention, polysulfone and zirconium oxide, are cheap and readily available, the preparation process is simple, and it is convenient for industrial expansion production;

[0038] 4. In the present invention, the pore size of the supporting base network 1 is preferably 200-500 μm, which can enhance the mechanical strength of the composite diaphragm; the hydrophilic slurry is preferably composed of a polymer binder, a porogen, a hydroxide ion transfer carrier and hydrophilic metal oxide particles in a mass ratio of (15-30):(5-30):(0-30):(30-60), wherein the hydroxide ion transfer carrier can enhance the hydroxide transfer capacity of the composite diaphragm; the hydrophilic metal oxide particles are preferably zirconium oxide, titanium oxide, magnesium oxide, cerium oxide, barium sulfate or barium titanate, with a particle size of 50-200 nm, which can enhance the hydrophilicity of the composite diaphragm; the coagulation bath temperature is preferably between 10-60°C, the non-solvent induced phase inversion time is 10-60 min, and the coagulation bath is preferably deionized water, which can enable the hydrophilic slurry to form a relatively uniform microporous structure during the phase inversion process.

[0039] In summary, the present invention strengthens the transfer of hydroxide ions by constructing a hydrogen bond network in the diaphragm, thereby effectively reducing the surface resistance of the diaphragm while maintaining high air tightness of the diaphragm, thereby reducing the energy consumption of electrolysis, and has the characteristics of strong ion transmission ability, good gas barrier performance and good mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a schematic diagram of the structure of the alkaline water electrolysis hydrogen production diaphragm for enhancing hydroxide ion transfer provided by the present invention.

[0041] Figure 2 A schematic diagram of the hydroxide ion transfer mechanism in the alkaline water electrolysis hydrogen production membrane for enhanced hydroxide ion transfer provided by the present invention.

[0042] Figure 3 These are SEM images of the diaphragm obtained in Example 3 of the present invention, wherein a) is a SEM image of the diaphragm surface, and b) is a SEM image of the diaphragm cross-section.

[0043] Figure 4 This is a comparison chart of the membrane surface resistance provided by the embodiments of the present invention and the comparative examples.

[0044] Figure 5 This is a tension-displacement curve diagram of the diaphragm obtained in Example 3 of the present invention.

[0045] In the figure: 1. Support base mesh; 2. Hydrophilic air barrier coating. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0047] like Figure 1As shown, an alkaline water electrolysis hydrogen production diaphragm for strengthening hydroxide ion transfer comprises a supporting base mesh 1, and hydrophilic gas barrier coatings 2 containing hydroxide ion transfer carriers are respectively arranged on both sides of the supporting base mesh 1; the material of the supporting base mesh 1 is any one of polyphenylene sulfide, polypropylene or polytetrafluoroethylene; the pore size of the supporting base mesh 1 is 200-500 μm; the hydrophilic gas barrier coating 2 comprises a hydroxide ion transfer carrier, a polymer binder and hydrophilic metal oxide particles; the hydroxide ion transfer carrier is any one of polybenzimidazole, polyethylene glycol, polyvinyl alcohol or polyethyleneimine polymer additives, or layered double metal hydroxide inorganic additives or any combination of two or more in any ratio; the polymer binder is any one of polysulfone, polyphenylsulfone or polyethersulfone or any combination of two or more in any ratio; the hydrophilic metal oxide particles are any one of zirconium oxide, titanium oxide, magnesium oxide, cerium oxide, barium sulfate or barium titanate or any combination of two or more in any ratio; the particle size of the hydrophilic metal oxide particles is 50-200 nm.

[0048] Example 1

[0049] This embodiment provides an alkaline water electrolysis hydrogen production diaphragm material for enhancing hydroxide ion transfer, and the preparation process is as follows:

[0050] Step S1, pre-treating the support base mesh 1: using deionized water to remove impurities and dust on the surface of the support base mesh;

[0051] Step S2, preparing a hydrophilic slurry: dissolving 10 g of polysulfone resin and 7.5 g of polyvinyl pyrrolidone in 55 g of N-methylpyrrolidone (NMP) for standby use; then uniformly dispersing 30 g of zirconium oxide and 7.5 g of polybenzimidazole therein to obtain a hydrophilic slurry; slowly stirring for 24 hours for degassing; the hydrophilic slurry is composed of polysulfone resin: polyvinyl pyrrolidone: polybenzimidazole: zirconium oxide in a mass ratio of 18:14:14:54;

[0052] Step S3, coating the hydrophilic slurry on both sides of the support base mesh 1: scraping the hydrophilic slurry obtained in step S2 on both sides of the support base mesh 1 to obtain a liquid film with a thickness of 550 μm;

[0053] Step S4, performing phase transformation on the hydrophilic slurry layer to form a hydrophilic air barrier coating 2: pre-evaporating the liquid film at room temperature for 5 seconds, immersing it in 10° C. deionized water for non-solvent induced phase transformation, and forming a hydrophilic air barrier coating 2 on both sides of the support base mesh after 10 minutes;

[0054] Step S5, post-treating the diaphragm: soaking the diaphragm obtained in step S4 in deionized water to remove the solvent in the membrane, thereby obtaining an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer and a thickness of 453 μm.

[0055] An alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer prepared by the method comprises a supporting base mesh 1, and hydrophilic gas barrier coatings 2 containing hydroxide ion transfer carriers are respectively arranged on both sides of the supporting base mesh 1; the material of the supporting base mesh 1 is polyphenylene sulfide; the pore size of the supporting base mesh 1 is 425 μm; the hydrophilic gas barrier coating 2 comprises a hydroxide ion transfer carrier, a polymer binder and hydrophilic metal oxide particles; the hydroxide ion transfer carrier is polybenzimidazole; the polymer binder is polysulfone; the hydrophilic metal oxide particles are zirconium oxide; and the particle size of the hydrophilic metal oxide particles is 150 nm.

[0056] The diaphragm prepared by this method can reduce the diaphragm surface resistance by 36%, and the bubble point pressure can reach 4 bar.

[0057] Example 2

[0058] This embodiment provides an alkaline water electrolysis hydrogen production diaphragm material for enhancing hydroxide ion transfer, and the preparation process is as follows:

[0059] Step S1, pre-treating the support base mesh 1: using ethanol to remove impurities and dust on the surface of the support base mesh;

[0060] Step S2, preparing a hydrophilic slurry: dissolving 10 g of polysulfone resin and 7.5 g of polyvinyl pyrrolidone in 50 g of N-methylpyrrolidone (NMP) for standby use; then uniformly dispersing 30 g of zirconium oxide and 7.5 g of polyethylene glycol therein to obtain a hydrophilic slurry; slowly stirring for 24 hours for degassing; the hydrophilic slurry is composed of polysulfone resin: polyvinyl pyrrolidone: polyethylene glycol: zirconium oxide in a mass ratio of 18:14:14:54;

[0061] Step S3, coating the hydrophilic slurry on both sides of the support base mesh 1: scraping the hydrophilic slurry obtained in step 2 on both sides of the support base mesh to obtain a liquid film with a thickness of 550 μm;

[0062] Step 4: Phase inversion of the hydrophilic slurry layer to form a hydrophilic air-barrier coating: pre-evaporating the liquid film at room temperature for 15 seconds, immersing it in 15° C. deionized water for non-solvent-induced phase inversion, and forming a hydrophilic air-barrier coating on both sides of the support base mesh after 20 minutes;

[0063] Step 5: Post-treat the diaphragm: Soak the diaphragm obtained in step 4 in deionized water to remove the solvent in the membrane, thereby obtaining an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer and a thickness of 460 μm.

[0064] The method is used to prepare an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer, comprising a supporting base mesh 1, and hydrophilic gas barrier coatings 2 containing hydroxide ion transfer carriers are respectively arranged on both sides of the supporting base mesh 1; the material of the supporting base mesh 1 is polyphenylene sulfide; the pore size of the supporting base mesh 1 is 425 μm; the hydrophilic gas barrier coating 2 comprises a hydroxide ion transfer carrier, a polymer binder and hydrophilic metal oxide particles; the hydroxide ion transfer carrier is polyethylene glycol; the polymer binder is polysulfone; the hydrophilic metal oxide particles are zirconium oxide; and the particle size of the hydrophilic metal oxide particles is 150 nm.

[0065] The diaphragm prepared by this method can reduce the diaphragm surface resistance by 36%, and the bubble point pressure can reach 4 bar.

[0066] Example 3

[0067] This embodiment provides an alkaline water electrolysis hydrogen production diaphragm material for enhancing hydroxide ion transfer, and the preparation process is as follows:

[0068] Step S1, pre-treating the support base mesh 1: first using deionized water and then using ethanol to remove impurities and dust on the surface of the support base mesh;

[0069] Step S2, preparing a hydrophilic slurry: dissolving 10 g of polysulfone resin and 7.5 g of polyvinyl pyrrolidone in 48 g of N-methylpyrrolidone (NMP) for standby use; then uniformly dispersing 30 g of zirconium oxide and 7.5 g of layered double metal hydroxide therein to obtain a hydrophilic slurry; slowly stirring for 24 hours for degassing; the hydrophilic slurry consists of polysulfone resin: polyvinyl pyrrolidone: layered double metal hydroxide: zirconium oxide in a mass ratio of 18:14:14:54;

[0070] Step S3, coating the hydrophilic slurry on both sides of the support base mesh 1: scraping the hydrophilic slurry obtained in step S2 on both sides of the support base mesh 1 to obtain a liquid film with a thickness of 550 μm;

[0071] Step S4, performing phase transformation on the hydrophilic slurry layer to form a hydrophilic air barrier coating 2: pre-evaporating the liquid film at room temperature for 60 seconds, immersing it in 30°C deionized water for non-solvent induced phase transformation, and forming a hydrophilic air barrier coating on both sides of the support base mesh after 30 minutes;

[0072] Step S5, post-treating the diaphragm: soaking the diaphragm obtained in step 4 in deionized water to remove the solvent in the membrane, thereby obtaining an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer and a thickness of 444 μm.

[0073] The method is used to prepare an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer, comprising a supporting base mesh 1, and hydrophilic gas barrier coatings 2 containing hydroxide ion transfer carriers are respectively arranged on both sides of the supporting base mesh 1; the material of the supporting base mesh 1 is polyphenylene sulfide; the pore size of the supporting base mesh 1 is 425 μm; the hydrophilic gas barrier coating 2 comprises a hydroxide ion transfer carrier, a polymer binder and hydrophilic metal oxide particles; the hydroxide ion transfer carrier is a layered double metal hydroxide; the polymer binder is polysulfone; the hydrophilic metal oxide particles are zirconium oxide; and the particle size of the hydrophilic metal oxide particles is 150 nm.

[0074] The diaphragm prepared by this method can reduce the diaphragm surface resistance by 43%, and the bubble point pressure can reach 4 bar.

[0075] Example 4

[0076] This embodiment provides an alkaline water electrolysis hydrogen production diaphragm material for enhancing hydroxide ion transfer, and the preparation process is as follows:

[0077] Step S1, pre-treating the support base mesh 1: first using deionized water and then using ethanol to remove impurities and dust on the surface of the support base mesh;

[0078] Step S2, preparing a hydrophilic slurry: dissolving 10 g of polysulfone resin and 5 g of polyvinyl pyrrolidone in 46 g of N-methylpyrrolidone (NMP) for standby use; then uniformly dispersing 30 g of zirconium oxide and 10 g of layered double metal hydroxide therein to obtain a hydrophilic slurry; slowly stirring for 24 hours for degassing; the hydrophilic slurry consists of polysulfone resin: polyvinyl pyrrolidone: layered double metal hydroxide: zirconium oxide in a mass ratio of 18:9:19:54;

[0079] Step S3, coating the hydrophilic slurry on both sides of the support base mesh 1: scraping the hydrophilic slurry obtained in step S2 on both sides of the support base mesh 1 to obtain a liquid film with a thickness of 550 μm;

[0080] Step S4, performing phase transformation on the hydrophilic slurry layer to form a hydrophilic gas barrier coating 2: pre-evaporating the liquid film at room temperature for 75 seconds, immersing it in 45°C deionized water for non-solvent induced phase transformation, and forming a hydrophilic gas barrier coating on both sides of the support base mesh after 40 minutes;

[0081] Step S5, post-treating the diaphragm: soaking the diaphragm obtained in step 4 in deionized water to remove the solvent in the membrane, thereby obtaining an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer and a thickness of 436 μm.

[0082] The method is used to prepare an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer, comprising a supporting base mesh 1, and hydrophilic gas barrier coatings 2 containing hydroxide ion transfer carriers are respectively arranged on both sides of the supporting base mesh 1; the material of the supporting base mesh 1 is polyphenylene sulfide; the pore size of the supporting base mesh 1 is 425 μm; the hydrophilic gas barrier coating 2 comprises a hydroxide ion transfer carrier, a polymer binder and hydrophilic metal oxide particles; the hydroxide ion transfer carrier is a layered double metal hydroxide; the polymer binder is polysulfone; the hydrophilic metal oxide particles are zirconium oxide; and the particle size of the hydrophilic metal oxide particles is 150 nm.

[0083] The diaphragm prepared using this method can reduce the diaphragm surface resistance by 43%, and the bubble point pressure can reach 3.7 bar.

[0084] Example 5

[0085] This embodiment provides an alkaline water electrolysis hydrogen production diaphragm material for enhancing hydroxide ion transfer, and the preparation process is as follows:

[0086] Step S1, pre-treating the support base mesh 1: first using deionized water and then using ethanol to remove impurities and dust on the surface of the support base mesh;

[0087] Step S2, preparing a hydrophilic slurry: dissolving 10g of polysulfone resin and 10g of polyvinyl pyrrolidone in 51g of N-methylpyrrolidone (NMP) for standby use; then uniformly dispersing 30g of zirconium oxide and 5g of layered double metal hydroxide therein to obtain a hydrophilic slurry; slowly stirring for 24h for degassing; the hydrophilic slurry consists of polysulfone resin: polyvinyl pyrrolidone: layered double metal hydroxide: zirconium oxide in a mass ratio of 18:19:9:54;

[0088] Step S3, coating the hydrophilic slurry on both sides of the support base mesh 1: scraping the hydrophilic slurry obtained in step S2 on both sides of the support base mesh 1 to obtain a liquid film with a thickness of 550 μm;

[0089] Step S4, performing phase transformation on the hydrophilic slurry layer to form a hydrophilic gas barrier coating 2: pre-evaporating the liquid film at room temperature for 100 seconds, immersing it in 30° C. deionized water for non-solvent induced phase transformation, and forming a hydrophilic gas barrier coating on both sides of the support base mesh after 45 minutes;

[0090] Step S5, post-treating the diaphragm: soaking the diaphragm obtained in step 4 in deionized water to remove the solvent in the membrane, thereby obtaining an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer and a thickness of 453 μm.

[0091] The method is used to prepare an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer, comprising a supporting base mesh 1, and hydrophilic gas barrier coatings 2 containing hydroxide ion transfer carriers are respectively arranged on both sides of the supporting base mesh 1; the material of the supporting base mesh 1 is polyphenylene sulfide; the pore size of the supporting base mesh 1 is 425 μm; the hydrophilic gas barrier coating 2 comprises a hydroxide ion transfer carrier, a polymer binder and hydrophilic metal oxide particles; the hydroxide ion transfer carrier is a layered double metal hydroxide; the polymer binder is polysulfone; the hydrophilic metal oxide particles are zirconium oxide; and the particle size of the hydrophilic metal oxide particles is 150 nm.

[0092] The diaphragm prepared using this method can reduce the diaphragm surface resistance by 36%, and the bubble point pressure can reach 4.1 bar.

[0093] Example 6

[0094] This embodiment provides an alkaline water electrolysis hydrogen production diaphragm material for enhancing hydroxide ion transfer, and the preparation process is as follows:

[0095] Step S1, pre-treating the support base mesh 1: using ethanol to remove impurities and dust on the surface of the support base mesh;

[0096] Step S2, preparing a hydrophilic slurry: dissolving 10g of polysulfone resin and 10g of polyvinyl pyrrolidone in 55g of N-methylpyrrolidone (NMP) for standby use; then uniformly dispersing 30g of zirconium oxide and 5g of polybenzimidazole therein to obtain a hydrophilic slurry; slowly stirring for 24h for degassing; the hydrophilic slurry is composed of polysulfone resin: polyvinyl pyrrolidone: polybenzimidazole: zirconium oxide in a mass ratio of 18:19:9:54;

[0097] Step S3, coating the hydrophilic slurry on both sides of the support base mesh 1: scraping the hydrophilic slurry obtained in step S2 on both sides of the support base mesh 1 to obtain a liquid film with a thickness of 550 μm;

[0098] Step S4, performing phase transformation on the hydrophilic slurry layer to form a hydrophilic gas barrier coating 2: pre-evaporating the liquid film at room temperature for 120 seconds, immersing it in 60° C. deionized water for non-solvent induced phase transformation, and forming a hydrophilic gas barrier coating on both sides of the support base mesh after 60 minutes;

[0099] Step S5, post-treating the diaphragm: soaking the diaphragm obtained in step 4 in deionized water to remove the solvent in the membrane, thereby obtaining an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer and a thickness of 462 μm.

[0100] The method is used to prepare an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer, comprising a supporting base mesh 1, and hydrophilic gas barrier coatings 2 containing hydroxide ion transfer carriers are respectively arranged on both sides of the supporting base mesh 1; the material of the supporting base mesh 1 is polyphenylene sulfide; the pore size of the supporting base mesh 1 is 425 μm; the hydrophilic gas barrier coating 2 comprises a hydroxide ion transfer carrier, a polymer binder and hydrophilic metal oxide particles; the hydroxide ion transfer carrier is polybenzimidazole; the polymer binder is polysulfone; the hydrophilic metal oxide particles are zirconium oxide; and the particle size of the hydrophilic metal oxide particles is 150 nm.

[0101] The diaphragm prepared by this method can reduce the diaphragm surface resistance by 29%, and the bubble point pressure can reach 4 bar.

[0102] Comparative Example 1

[0103] This comparative example provides a composite diaphragm for commercial alkaline water electrolysis to produce hydrogen. The composite diaphragm is ZIRFON UTP 500+ produced by Agfa.

[0104] Comparative Example 2

[0105] This comparative example provides a composite diaphragm material for producing hydrogen by alkaline water electrolysis, and the preparation process thereof is as follows:

[0106] Step S1: pre-treating the support base mesh: removing impurities and dust on the surface of the support base mesh with deionized water;

[0107] Step S2: preparing a hydrophilic slurry: first, dissolving 10 g of polysulfone resin and 15 g of polyvinyl pyrrolidone in 55 g of N-methylpyrrolidone (NMP) for later use; uniformly dispersing 30 g of zirconium oxide therein to obtain a hydrophilic slurry; slowly stirring for 24 h for degassing;

[0108] Step S3: coating the hydrophilic slurry on both sides of the support base mesh: coating the hydrophilic slurry obtained in step 2 on both sides of the support base mesh by scraping to obtain a liquid film with a thickness of 550 μm;

[0109] Step S4: performing phase transformation on the hydrophilic slurry layer to form a hydrophilic air-barrier coating: pre-evaporating the liquid film at room temperature for 15 seconds, immersing it in 15° C. deionized water for non-solvent-induced phase transformation, and forming a hydrophilic air-barrier coating on both sides of the support base mesh after 30 minutes;

[0110] Step S5: Post-processing the diaphragm: Soak the diaphragm obtained in step S4 in deionized water to remove the solvent in the membrane, thereby obtaining a composite diaphragm for producing hydrogen by alkaline water electrolysis with a thickness of 462 μm.

[0111] Comparative Example 3

[0112] This comparative example provides a composite diaphragm material for producing hydrogen by alkaline water electrolysis, and the preparation process thereof is as follows:

[0113] Step S1: pre-treating the support base mesh: removing impurities and dust on the surface of the support base mesh with ethanol;

[0114] Step S2: preparing a hydrophilic slurry: first, dissolving 10 g of polysulfone resin and 15 g of polyvinyl pyrrolidone in 55 g of N-methylpyrrolidone (NMP) for later use; uniformly dispersing 40 g of zirconium oxide therein to obtain a hydrophilic slurry; slowly stirring for 24 h for degassing;

[0115] Step S3: coating the hydrophilic slurry on both sides of the support base mesh: coating the hydrophilic slurry obtained in step 2 on both sides of the support base mesh by scraping to obtain a liquid film with a thickness of 550 μm;

[0116] Step S4: Phase inversion of the hydrophilic slurry layer to form a hydrophilic air barrier coating: pre-evaporating the liquid film at room temperature for 15 seconds, immersing it in 15°C deionized water for non-solvent induced phase inversion, and forming a hydrophilic air barrier coating on both sides of the support base mesh after 30 minutes.

[0117] Step S5: Post-processing the diaphragm: Soak the diaphragm obtained in step S4 in deionized water to remove the solvent in the membrane, thereby obtaining a composite diaphragm for producing hydrogen by alkaline water electrolysis with a thickness of 456 μm.

[0118] Performance Testing

[0119] The membrane samples obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to structural and performance tests, including SEM, surface resistance, air tightness and mechanical strength. The results are shown in Table 1.

[0120] The surface resistance test method is as follows: soak the membrane sample in 30wt% KOH for more than 4 hours to make the membrane completely filled with electrolyte; then use an AC impedance meter to test the resistance difference between the two electrodes with and without the membrane, multiplying it by the effective area of ​​the membrane to get the surface resistance, repeat the measurement three times and take the average value as the surface resistance value of the sample;

[0121] The air tightness test method is as follows: the membrane sample is completely soaked with ultrapure water, and the bubble pressure method membrane pore size analyzer is used for testing. The instrument automatically determines the bubble point to reduce the test error. The measurement is repeated three times and the average value is taken as the bubble point pressure of the sample.

[0122] The mechanical strength test method is as follows: the diaphragm is cut into 80 mm × 10 mm long strip samples, and the tensile strength of the diaphragm is tested using an electronic universal testing machine and a constant speed tensile method, with a tensile speed of 100 mm / min.

[0123] Table 1

[0124] <![CDATA[Sheet Resistance / Ω·cm 2 > Bubble point pressure / bar Mechanical strength / MPa Example 1 0.09 4 32 Example 2 0.09 4 31 Example 3 0.08 4 29 Example 4 0.08 3.7 31 Example 5 0.09 4.1 29 Example 6 0.10 4 31 Comparative Example 1 0.14 4 30 Comparative Example 2 0.18 4 28 Comparative Example 3 0.15 2 26

[0125] As shown in Table 1, in Examples 1-6, the introduction of the hydroxide ion transfer carrier significantly reduced the membrane surface resistance, while maintaining a high bubble point pressure and membrane mechanical strength. Among them, the membrane obtained in Example 3 using layered double metal hydroxide as the hydroxide ion transfer carrier has the best comprehensive performance, and the surface resistance is reduced by 43%.

[0126] In summary, compared with the prior art, the alkaline water electrolysis hydrogen production diaphragm material prepared by the present invention has both low surface resistance and high air tightness, and has good mechanical strength. The preparation method of the alkaline water electrolysis hydrogen production diaphragm provided by the present invention introduces polar groups such as hydroxyl, amino, and carboxyl groups into the traditional composite diaphragm to construct a hydrogen bond network, so that the hydroxide ions can be transferred in the membrane along the dynamic hydrogen bond network to promote the transfer of hydroxide ions, and finally improve the performance of the diaphragm.

Claims

1. An alkaline water electrolysis hydrogen production diaphragm for enhancing hydroxide ion transfer, characterized in that: The invention comprises a supporting base net (1), and hydrophilic gas-isolating coatings (2) containing a hydroxide ion transfer carrier are respectively arranged on both sides of the supporting base net (1).

2. The alkaline water electrolysis hydrogen production diaphragm for enhancing hydroxide ion transfer according to claim 1, characterized in that: The material of the supporting base net 1 is any one of polyphenylene sulfide, polypropylene or polytetrafluoroethylene.

3. The alkaline water electrolysis hydrogen production diaphragm for enhancing hydroxide ion transfer according to claim 1, characterized in that: The pore size of the supporting base net (1) is 200-500 μm.

4. The alkaline water electrolysis hydrogen production diaphragm for enhancing hydroxide ion transfer according to claim 1, characterized in that: The hydrophilic gas barrier coating (2) comprises a hydroxide ion transfer carrier, a polymer binder and hydrophilic metal oxide particles; the hydrophilic slurry comprises the polymer binder, the porogen, the hydroxide ion transfer carrier and the hydrophilic metal oxide particles in a mass ratio of (15-30):(5-30):(0-30):(30-60).

5. The alkaline water electrolysis hydrogen production diaphragm for enhancing hydroxide ion transfer according to claim 4, characterized in that: The hydroxide ion transfer carrier is any one of polybenzimidazole, polyethylene glycol, polyvinyl alcohol, polyethyleneimine or layered double metal hydroxide or any combination of two or more thereof in any ratio; the polymer binder is any one of polysulfone, polyphenylsulfone or polyethersulfone or any combination of two or more thereof in any ratio; the hydrophilic metal oxide particles are any one of zirconium oxide, titanium oxide, magnesium oxide, cerium oxide, barium sulfate or barium titanate or any combination of two or more thereof in any ratio; the particle size of the hydrophilic metal oxide particles is 50 to 200 nm.

6. A method for preparing an alkaline water electrolysis hydrogen production membrane for enhancing hydroxide ion transfer according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1: pre-processing the supporting base network 1: Use deionized water or ethanol to remove impurities and dust on the surface of the support base mesh; Step S2, preparing hydrophilic slurry: The polymer binder and the porogen are dissolved in a good solvent for later use; the hydrophilic metal oxide particles and the hydroxide ion transfer carrier are evenly dispersed in the good solvent in which the polymer binder and the porogen are dissolved to obtain a hydrophilic slurry; Step S3, coating the hydrophilic slurry on both sides of the supporting base mesh 1: The hydrophilic slurry obtained in step S2 is uniformly coated on both sides of the supporting base mesh 1 to obtain a liquid film with a thickness of 400 to 600 μm. Step S4, performing phase transformation on the hydrophilic slurry layer to form a hydrophilic air barrier coating 2: The liquid film obtained in step S3 is subjected to a steam-induced phase transformation for 5-120 seconds and then immersed in a coagulation bath for a non-solvent-induced phase transformation. The coagulation bath temperature is between 10-60° C. and the non-solvent-induced phase transformation time is 10-60 minutes, forming a hydrophilic gas barrier coating 2 on both sides of the support base mesh; Step S5, post-processing the diaphragm: The membrane obtained in step S4 is immersed in deionized water to remove the good solvent used in preparing the hydrophilic slurry in the membrane, thereby obtaining an alkaline water electrolysis hydrogen production membrane with enhanced hydroxide ion transfer and a thickness of 300 to 600 μm.

7. The method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis with enhanced hydroxide ion transfer according to claim 6, characterized in that: The porogen in step S2 is polyvinyl pyrrolidone; the good solvent in step S2 is one of N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylformamide.

8. The method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis with enhanced hydroxide ion transfer according to claim 6, characterized in that: The hydrophilic slurry in step S2 includes a polymer binder, a porogen, a hydroxide ion transfer carrier and hydrophilic metal oxide particles in a mass ratio of (15-30):(5-30):(0-30):(30-60); the viscosity of the hydrophilic slurry in step S2 is 10-25 Pa·s.

9. The method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis with enhanced hydroxide ion transfer according to claim 6, characterized in that: The coagulation bath in step S4 is preferably deionized water.

10. A method for preparing a diaphragm material for alkaline water electrolysis hydrogen production with enhanced hydroxide ion transfer, characterized in that: The preparation process is: Step S1, pre-treating the support base mesh 1: first using deionized water and then using ethanol to remove impurities and dust on the surface of the support base mesh; Step S2, preparing a hydrophilic slurry: dissolving 10 g of polysulfone resin and 7.5 g of polyvinyl pyrrolidone in 48 g of N-methylpyrrolidone (NMP) for standby use; then uniformly dispersing 30 g of zirconium oxide and 7.5 g of layered double metal hydroxide therein to obtain a hydrophilic slurry; slowly stirring for 24 hours for degassing; the hydrophilic slurry consists of polysulfone resin: polyvinyl pyrrolidone: layered double metal hydroxide: zirconium oxide in a mass ratio of 18:14:14:54; Step S3, coating the hydrophilic slurry on both sides of the support base mesh 1: scraping the hydrophilic slurry obtained in step S2 on both sides of the support base mesh 1 to obtain a liquid film with a thickness of 550 μm; Step S4, performing phase transformation on the hydrophilic slurry layer to form a hydrophilic air barrier coating 2: pre-evaporating the liquid film at room temperature for 60 seconds, immersing it in 30°C deionized water for non-solvent induced phase transformation, and forming a hydrophilic air barrier coating on both sides of the support base mesh after 30 minutes; Step S5, post-treating the diaphragm: soaking the diaphragm obtained in step 4 in deionized water to remove the solvent in the membrane, thereby obtaining an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer having a thickness of 444 μm; The method is used to prepare an alkaline water electrolysis hydrogen production diaphragm with enhanced hydroxide ion transfer, comprising a supporting base mesh 1, and hydrophilic gas barrier coatings 2 containing hydroxide ion transfer carriers are respectively arranged on both sides of the supporting base mesh 1; the material of the supporting base mesh 1 is polyphenylene sulfide; the pore size of the supporting base mesh 1 is 425 μm; the hydrophilic gas barrier coating 2 comprises a hydroxide ion transfer carrier, a polymer binder and hydrophilic metal oxide particles; the hydroxide ion transfer carrier is a layered double metal hydroxide; the polymer binder is polysulfone; the hydrophilic metal oxide particles are zirconium oxide; and the particle size of the hydrophilic metal oxide particles is 150 nm.

Citation Information

Patent Citations

  • Non-asbestos alkaline electrolyzed water composite diaphragm and preparation method thereof

    CN114432905A

  • Preparation method of alkaline electrolytic water hydrogen production diaphragm and diaphragm

    CN115074763A

Cited By

  • Alkaline electrolyzed water diaphragm based on nickel oxyhydroxide as well as preparation method and application of alkaline electrolyzed water diaphragm

    CN120888978A

  • Alkaline electrolyzed water composite diaphragm based on hydroxyl alumina and preparation method of alkaline electrolyzed water composite diaphragm

    CN121556087A

  • Alumina oxyhydroxide-based alkaline electrolytic water composite separator and method for preparing the same

    CN121556087B

  • Alkaline electrolytic water hydrogen production diaphragm based on modified cerium oxide and preparation method thereof

    CN121653751A

  • A modified cerium oxide-based alkaline electrolytic water hydrogen production diaphragm and a preparation method thereof

    CN121653751B